Evaluating GPS sampling rates for pedestrian assistant systems. (2nd July 2016) - Schneider, Cornelia; Zutz, Sebastian; Rehrl, Karl; Brunauer, Richard; Gröchenig, Simon
Abstract: In recent years, assistant systems have come to widespread use and support people in various situations e.g. in getting from A to B. For quite a time also assistant systems with special attention to older people have been developed. For example, in case of cognitive impairments where autonomous living indoors as well as outdoors is affected, assistant systems can be valuable aids. First attempts for outdoor assistance with GPS-based location systems offering the possibility to define geo-fences for raising an alert if a known area is left have been made. The quality of these systems is largely dependent on the precision of localisation which among others is influenced by the sampling rate. This paper reports on an empirical study under real world conditions to determine a suitable GPS sampling rate for movement analysis of (cognitively impaired) pedestrians. The work considers GPS measurement and interpolation errors as well as track losses as a result of low sampling rates. For the study, GPS data for different environmental settings and movement scenarios for sampling rates of 1, 2, 3, 4, 5, 10, 15, 20 and 25 s has been collected. The impact of sampling rates on movement parameters like track length and speed has been empirically measured. Additionally, the influence of smoothing approaches on data quality and whether downsampling of data has the same effect as recording with corresponding lower sampling rate has been studied. Results show that across all tested scenarios a sampling rate of 3–5 s seems to be appropriate with respect to speed and track length. Additionally, it can be argued that smoothing improves data quality of highly sampled data (up to 4 s). With downsampling, outliers are less in comparison to data sampled at the corresponding sampling rate.